2020
DOI: 10.3389/fmicb.2020.01148
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Establishment and Maintenance of Germ-Free Rat Models

Abstract: Numerous studies have demonstrated that the gut microbiota plays a vital role in human health and disease development. Although the number of studies on host-microbiota interactions have increased in recent years, the underlying pathogenesis of dysbiosisrelated diseases are still largely unknown. Germ-free (GF) rodent models, with the animals housed in sterile isolators and completely free of microbiota, are useful tools to advance our understanding of host-microbiota relationship in vivo. Although protocols c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The dynamics of bacterial colonization with Li01 in the intestines were investigated in a germ-free SD rat model. Ten male germ-free rats (6-8 weeks old) were maintained according to the methods we established previously 58 . Germ-free rats were fed through gavage with 200 µL of solution containing 10 9 CFU/mL of non-encapsulated Li01 (n = 5) or LbL Li01 (n = 5).…”
Section: Bacterial Colonization In Germ-free Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of bacterial colonization with Li01 in the intestines were investigated in a germ-free SD rat model. Ten male germ-free rats (6-8 weeks old) were maintained according to the methods we established previously 58 . Germ-free rats were fed through gavage with 200 µL of solution containing 10 9 CFU/mL of non-encapsulated Li01 (n = 5) or LbL Li01 (n = 5).…”
Section: Bacterial Colonization In Germ-free Ratsmentioning
confidence: 99%
“…npj Biofilms and Microbiomes (2021)58 Published in partnership with Nanyang Technological University…”
mentioning
confidence: 99%
“…More interestingly, in GF rats, Sennoside A did not lower the ratio of abnormal EEG, or lower TNF-α, IL-1β, and IL-6 levels in rat cortexes. Abnormal EEG and elevated in ammatory mediators indicate the degree of SAE [14] . The present results support the hypothesis that gut microbiota is involved in the pathogenesis of LPS-associated encephalopathy and that Sennoside A exerts its brain protective effects through gut microbiota alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were housed under a 12-h light/dark cycle in a temperature-controlled room at 24±1°C with free access to food and water. Germ free rats were given free access to germ free food and water (all food, water, bedding and other supplies that were put in the isolator were sterilized in advance) [14] .…”
Section: Animalsmentioning
confidence: 99%
“…We found that oxidized LA diet altered gut microbiota and failed to promote colitis in antibiotic-treated mice. In our study we did not use the approach of germ-free mice, because it usually requires irradiation to create sterile feed for germ-free mice 25 ; but during this process, the prepared experimental oils (e.g., puri ed corn oil and oxidized corn oil) added in the diets would be degraded and/or oxidized. In addition, we found that oxidized LA diet activated TLR4 signaling in vivo and failed to promote colitis in Tlr4 -/mice.…”
Section: Discussionmentioning
confidence: 99%